2014
DOI: 10.1007/s10886-014-0521-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Stereochemistry of the Aggregation Pheromone of Harlequin Bug, Murgantia histrionica

Abstract: Preparation of a complete stereoisomeric library of 1,10-bisaboladien-3-ols and selected 10,11-epoxy-1-bisabolen-3-ols was pivotal for the identification of the aggregation pheromone of the brown marmorated stink bug, Halyomorpha halys. Herein, we describe syntheses of the remaining 10,11-epoxy-1-bisabolen-3-ols, and provide additional evidence on the assignment of relative and absolute configurations of these compounds by single-crystal X-ray crystallography of an intermediate, (3S,6R,7R,10S)-1-bisabolen-3,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…Moreover, in other pentatomid bugs, male-produced compounds act as sex pheromones attracting only females, such as in Piezodorus guildinii (Westwood) [32], T. pallidovirens [33], Oebalus poecilus (Dallas) [34], Eysarcoris parvus (Uhler) [35], and Pallantia macunaima (Grazia) [36]. In other cases, the male-produced compounds act as aggregation pheromones, attracting females, males, and even nymphs, such as in Murgantia histrionica (Hahn) [37,38], N. viridula [27], Eysarcoris lewisi (Distant) [39], Euschistus tristigmus (Say) [18,30], and H. halys [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in other pentatomid bugs, male-produced compounds act as sex pheromones attracting only females, such as in Piezodorus guildinii (Westwood) [32], T. pallidovirens [33], Oebalus poecilus (Dallas) [34], Eysarcoris parvus (Uhler) [35], and Pallantia macunaima (Grazia) [36]. In other cases, the male-produced compounds act as aggregation pheromones, attracting females, males, and even nymphs, such as in Murgantia histrionica (Hahn) [37,38], N. viridula [27], Eysarcoris lewisi (Distant) [39], Euschistus tristigmus (Say) [18,30], and H. halys [40].…”
Section: Discussionmentioning
confidence: 99%
“…In a laboratory setting, Zahn et al [11,12] showed that an aggregation pheromone emitted by adult males feeding on a plant host was attractive to both sexes of adults, and concluded that the pheromone was a single isomer of 10,11-epoxy-1-bisabolen-3-ol [4-[3-(3,3-dimethyloxiran-2-yl)-1-methylpropyl]-1-methylcyclohex-2-en-1-ol], dubbed murgantiol. Khrimian et al [13] showed that the pheromone consisted of two stereoisomers, (3 S ,6 S ,7 R ,10 S )- and (3 S ,6 S ,7 R ,10 R )-10,11-epoxy-1-bisabolen-3-ol, which occur in a ~1.4:1 ratio in emissions of adult male harlequin bug. Weber et al [14] demonstrated that, in the field, lures containing a synthetic eight-stereoisomer blend were of comparable attractiveness with pure pheromone components to both sexes in adults, as well as to nymphs, and that presence of a host plant (collard) increased this attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…17 Intrigued by a significant mitigation of the loss of enantiopurity when KOH/Bu 4 NOH was replaced by LiOH/iPrOH (89% ee, or 94.5:5.5 S/R), 17 we became interested in using this base system for cyclizations of ketoaldehydes 8 and 9. Thus, stirring aldehydes 8 and 9 in an 10% isopropanol solution of lithium hydroxide hydrate at 25 o C for 5 h proceeded without significant epimerization and provided ketones 6 and 7 in 66% and 67% yields, respectively, and 92:8 dr (SM=Supplementary Material, p. [6][7][8]. We also found that lithium hydroxide hydrate as a source of LiOH provided a more reproducible and better stereochemical output than anhydrous lithium hydroxide, and the cyclization is facilitated by an initial ultrasonication.…”
Section: Resultsmentioning
confidence: 65%
“…9 This conveniently provided two single stereoisomers from one reaction (Scheme 1) and thus allowed us to build a full library of stereoisomers of bisaboladienols and epoxybisabolenols. 8,9 Scheme 1. Previous approach (Ref.…”
Section: Introductionmentioning
confidence: 99%